PENGEMBANGAN FORMULA MAKANAN ANAK BATITA MENGGUNAKAN PANGAN TRADISIONAL DADIH SUSU SAPI - Uken S. Soetrisno; Rossi R. Apriyantono; Nelis Imanningsih; Luxy Pasaribu (Persagi, 2000)
DEVELOPMENT OF FOOD FORMULA BASED ON FERMENTED COW'S MILK (DADIH) FOR CHILDREN UNDER THREE YEARS OLD.Background: Undernutrition is still one of major problems among children under three years old. One proposed strategic to overcome such problem is to give food supplementation to the children by using local materials.Objective: This study tried to use dadih as traditionally fermented milk from West Sumatera and developed into nutritious food formula.Method: Two kinds of carbohydrates were used in food product development with addition of dadih and tempe flour as protein sources. Physical characteristics and nutrient content were analyzed and prepared to fulfill the CAC criteria. The products acceptance was evaluated by sensoric or organoleptic tests which were done by adult women and by the target group.Results: The food products were nutritionally densed and highly accepted by the target group. The children could consume the product to fullfill their daily need for energy and protein as much as 25% and 50%, respectivelly. Different types of processing the formula should be done to produce different physical characteristics that could produce different types of snack foods.Key Words: dadih, fermented milk, food formula, children under three years old